Aspects and characterization of chert alteration in an archaeological context: A qualitative to quantitative pilot study. (August 2018) - Caux, Solene; Galland, Aline; Queffelec, Alain; Bordes, Jean-Guillaume
Abstract: Chert alteration in Paleolithic contexts, generally known as "patina" by prehistorians, has long been recognized. Originally, different types of "patina" were defined as "white patina", "glossy patina", or "porcelain-like patina", all of which involved changes in the color and/or roughness of the initial raw material. Alteration degrees are used in many research fields like taphonomy, petroarchaeology or use-wear analysis; however most of these studies are still based on qualitative descriptions using a wide range of terms that bring about confusion. In this paper, we present first the results of an inter-observer's blind-test where color and roughness are described at macroscopic scale. Secondly, we use quantitative methods to compare archaeological and experimental altered silicifications: light spectrometry and confocal microscopy are used to quantify color and roughness. We show here how macroscopic qualitative descriptions could lead to confusion because of the lack of calibration and the number of terms used differently by each one. We demonstrated the efficiency of quantitative methods as light spectrometry and confocal microscopy that will significantly enhance studies of surface alteration in terms of taphonomy, use-wear analyses, and petroarchaeology issues as well as interdisciplinary discussions. Highlights: In Paleolithic contexts, different types of «patina» are defined based on empiric and qualitative description. Here we offer to quantify the main alteration known as «white patina». We use light spectrometry to quantify color. We use confocal microscopy to quantify roughness. We compare archaeological and experimental altered material.